Problematika Perencanaan Strategis dalam Manajemen Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
Strategic planning is a fundamental component of Islamic educational management that plays a pivotal role in determining institutional development, improving educational quality, and strengthening organizational capacity to respond to dynamic environmental changes. However, its implementation continues to encounter various challenges that hinder effective institutional governance, including weak strategy formulation, limited stakeholder integration, and inadequate implementation and evaluation systems oriented toward continuous quality improvement. This study aims to comprehensively examine the challenges of strategic planning in Islamic educational management and identify the factors influencing its effectiveness. The study employed a qualitative method using a library research approach. Data were collected through a systematic review and critical analysis of scholarly journal articles, academic books, policy documents, and other scientific publications relevant to strategic management and Islamic educational management. Data were analyzed using qualitative content analysis through the stages of data reduction, categorization, interpretation, synthesis, and conclusion drawing to develop a comprehensive conceptual framework. The findings reveal that the challenges of strategic planning in Islamic educational management are multidimensional and encompass three major aspects: weak strategy formulation that is not grounded in comprehensive strategic environmental analysis; fragmented governance resulting from insufficient integration of leadership, stakeholder participation, and organizational culture; and limited capacity for strategy implementation and evaluation in responding to the digital transformation of education. Furthermore, the study demonstrates that effective strategic planning requires the integration of contemporary strategic management principles with the fundamental values of Islam, including amanah (trustworthiness), shūrā (consultative decision-making), ʿadl (justice), itqān (professional excellence), and maṣlaḥah (public benefit), to establish educational governance that is adaptive, participatory, accountable, and committed to sustainable quality enhancement. This study contributes conceptually to the advancement of Islamic educational management scholarship while providing a theoretical foundation for strengthening strategic planning practices that are more responsive to the challenges of education in the era of global transformation.